If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 4t = 2v Solving X + 4t = 2v Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4t' to each side of the equation. X + 4t + -4t = -4t + 2v Combine like terms: 4t + -4t = 0 X + 0 = -4t + 2v X = -4t + 2v Simplifying X = -4t + 2v
| 5x-1+5x-1+3x+3x= | | 3y+5=37-y | | 4(x+14)-x(x+14)= | | 4-4(n+4)=3+n | | 4x-42=-12+x+15 | | 11x-51=6x-13 | | 24x^8y^8+96x^6y^5-36x^3y^2= | | 3(7x-2)=27 | | 11y=21+4y | | 8x-20y=28 | | x-2/2+1-2x=x/10-2/5 | | 35y=48+29y | | 9n+14=5n+18 | | 3(x+4)-7=-10 | | 4y=18+y | | x-12/2+x/2+3/4=x | | 4b+19-(-6b)=-21 | | 42x^7y^9-30x^3y^7-30x^5y^5= | | 3-i=x | | 10*x+4-x*4=52 | | 10*x=52 | | 8x=-30 | | 4a=19-5 | | 3f-5+2f+6=26 | | 45-5x=95-9x | | 178=112-y | | 10*x+y-x*y=52 | | 3x+64=3 | | 6b+53=149 | | 18x^4y^6+21xy^3+9z^2= | | 2b+6=6b-10 | | 24=11w-3w |